Interrogating Homophobic Violence in a Public High School in Northern Chile [el Baile de Las Que Sobran. Interrogando la Violencia Homofóbica en Un Liceo Público Chileno] - Barrientos-Delgado, J (Inst. fur Klinische Psychologie und Gemeindepsychologie, 2018)
In this article we present a study on how homophobic violence (HV) toward women is carried out in schools. Concepts such as homophobic bullying or HV are commonly used to argue that this type of victimization is a response to hostile relations that occur to a greater degree among students. We performed a 6-month ethnographic study in a public high school in the city of Antofagasta, Chile. Critical discourse analysis was used to analyze our field notes, interviews with students, principals and teachers, and internal school regulations. The main findings indicate that the recent change in educational policies have influenced the organization of the school, in terms of incorporating complex tolerance exercises, vigilance, and regulation of the affective relationships among students. In addition, a series of practices had been promoted that include the imposition of heterosexual femininity. We conclude that heterosexuality operates as a policy management system in schools, producing zones of exclusion and reinforcing social hierarchies. Thus, in order to understand the articulation of HV, it is necessary to understand it as systemic arrangement within the school, given that this violence includes other expressions of violence, such as gender and class, and HV must also be understood in terms of heterosexual regulation exercises. © 2018, Inst. fur Klinische Psychologie und Gemeindepsychologie. All Rights Reserved.